Marketing Strategy Analysis on Sales Performance as a Basis for Managerial Decision Making (Case Study at Perum BULOG Kerinci Branch Office) - Selia Meilantika; Fredy Olimsar; Wirmie Eka Putra; Yuliusmanÿ (International Journal of Business and Quality Research, 2026)
This research is based on the marketing of Our Products, where in the marketing of Our Products there are still many people who do not or do not know what products are owned by Perum BULOG, even though the prices offered are relatively cheap. This causes competitiveness with other products to be weak and only a few people know Our Products. This condition also has an impact on the less than optimal sales performance of Our Products, so that the right marketing strategy is needed as a basis for managerial decision making. The purpose of this study is to determine what strategies are used by Perum BULOG in attracting consumer buying interest, improving sales performance, and supporting managerial decision making on Our Products. This study employed qualitative methods. Data were collected through interviews and direct field observations. The results indicate that Perum BULOG's marketing strategy for Our Products includes opening fostered outlets (RPK), conducting market operations, bazaars, and product promotions. This strategy has resulted in increased public purchasing interest and sales performance, which subsequently serves as a basis for management in determining marketing and business development policies.